Структурні трансформації національного промислового комплексу в контексті постіндустріального розвитку - Захарченко, В.І. (Економіка промисловості, 2017)
Виокремлено часткові структури (структурні аспекти) національного промислового комплексу (НПК): видів економічної діяльності, функціональну, секторальну, відтворювальну, інституційну, технологічну, зовнішньоторговельну, територіальну та інші. Запропоновано методичний інструментарій для структурного аналізу НПК. У розрізі часткових структур проаналізовано трансформаційні зміни у НПК України. У контексті постіндустріального розвитку визначено стратегічні напрями державної політики щодо трансформації структури НПК України. Выделены частные структуры (структурные аспекты) национального промышленного комплекса (НПК): видов экономической деятельности, функциональную, секторальную, воспроизводственную, институциональную, технологическую, внешнеторговую, территориальную и др. Предложен методический инструментарий для структурного анализа НПК. В разрезе частных структур проанализированы трансформационные изменения в НПК Украины. В контексте постиндустриального развития определены стратегические направления государственной политики относительно трансформации структуры НПК Украины. The partial structures (structural aspects) of national industrial complex (NIС) are marked out in the article, which are as follows: economic activities, functional, sectoral, reproductive, institutional, technological, foreign trade, territorial and others. In the context of market reforms and post-industrial development the article highlights positive changes in the structure of economic activity, institutional, technological and other structures of the NIC. The methodical tools for structural analysis of the NIС is suggested, which includes factors and indexes that characterize shares of economic activities or certain changes in these shares and the structure of the complex as a whole, and the degree of diversification of the complex structure (based on modified Herfindahl-Hirschman Index). In terms of partial structures transformational changes in the NIС of Ukraine are analyzed and major "structural imbalances" are found in it, namely the dominance of raw material and energy consuming activities (food processing, metallurgy and chemical industry), and the decrease of the most innovative activities including engineering. In the context of post-industrial development the author defines the strategic directions of the state policy of Ukraine in transforming the structure of the NIС. It is anticipated to accelerate the development of economic activities in the fifth and sixth technological structures, characterized by innovation, high added value and strong export potential.